Monetary policy trade-offs in an estimated open-economy DSGE model - Malin Adolfson; Stefan Laséen; Jesper Lindé; Lars E.O. Svensson (Sveriges Riksbank, 2009)
This paper studies the transmission of shocks and the trade-offs between stabilizing CPI inflation and alternative measures of the output gap in Ramses, the Riksbank's empirical dynamic stochastic general equilibrium (DSGE) model of a small open economy. The main results are, first, that the transmission of shocks depends substantially on the conduct of monetary policy, and second, that the trade-off between stabilizing CPI inflation and the output gap strongly depends on which concept of potential output in the output gap between output and potential output is used in the loss function. If potential output is defined as a smooth trend this trade-off is much more pronounced compared to the case when potential output is defined as the output level that would prevail if prices and wages were flexible.
Keywords: E52; E58; 330; impulse responses; instrument rules; open-economy DSGE models; Optimal monetary policy; output gap; potential output; Schock; Gesamtwirtschaftliche Produktion; Inflationsrate; Geldpolitik; Dynamisches Gleichgewicht; Kleine offene Volkswirtschaft